THE EFFECTIVENESS OF THE UNION OF EUROPEAN FOOTBALL ASSOCIATIONS (UEFA) IN DEALING WITH RACISM - Butuna, Dahlan Yusuf; Ilkodar, Saptopo Bambang (Jurnal Paradigma, 2025)
This article examines the failure of the Union of European Football Association (UEFA) to address racism in the world of football. UEFA has enacted a number of rules to prevent and reduce racist acts in football matches. Facts show that racist acts, especially those carried out by supporters, during 2013 to 2019 actually increased. This article tries to answer the question of why the UEFA regime is ineffective in dealing with the problem of racism in the world of football. The analysis was carried out by borrowing the theory of regime effectiveness developed by Arild Underdal. The author collected data by literature study method. The results of the analysis show that the UEFA regime is ineffective in dealing with racist acts in football matches in Europe because: (1) the problem of racism originates outside the world of football so it is impossible to solve it by football organizations alone; (2) the perpetrator of racism is the supporter, while UEFA rules cannot be applied to the supporter; (3) the interests of UEFA members are not aligned with each other, making it difficult to achieve collaboration; and (4) the governing organs do not have the required capacity.